A Glucagon-Like Peptide-1 Receptor Agonist Lowers Weight by Modulating the Structure of Gut Microbiota - Zhao, Li; Chen, Yi; Xia, Fangzhen; Abudukerimu, Buatikamu; Zhang, Wen; Guo, Yuyu; Wang, Ningjian; Lu, Yingli (Frontiers in Endocrinology, 2018)
In addition to improving glucose metabolism, liraglutide, a glucagon-like peptide-1 receptor agonist, has weight-loss effects. The underlying mechanisms are not completely understood. The current study was performed to explore whether liraglutide could lower weight by modulating the composition of the gut microbiota in simple obese and diabetic obese rats. In our study, Wistar and Goto-Kakizaki (GK) rats were randomly treated with liraglutide or normal saline for 12 weeks. The biochemical parameters and metabolic hormones were measured. Hepatic glucose production and lipid metabolism were also assessed with isotope tracers. Changes in gut microbiota were analyzed by 16S rRNA gene sequencing. Both glucose and lipid metabolism were significantly improved by liraglutide. Liraglutide lowered body weight independent of glycemia status. The abundance and diversity of gut microbiota were considerably decreased by liraglutide. Liraglutide also decreased obesity-related microbial phenotypes and increased lean-related phenotypes. In conclusion, liraglutide can prevent weight gain by modulating the gut microbiota composition in both simple obese and diabetic obese subjects.